Effect of Honey and Eugenol on Ehrlich Ascites and Solid Carcinoma. (28th March 2010) - Jaganathan, Saravana Kumar; Mondhe, Dilip; Wani, Z. A.; Pal, Harish C.; Mandal, Mahitosh
Abstract : Ehrlich ascites carcinoma is a spontaneous murine mammary adenocarcinoma adapted to ascites form and carried in outbred mice by serial intraperitoneal (i/p) passages. The previous work from our laboratory showed that honey having higher phenolic content was potent in inhibiting colon cancer cell proliferation. In this work, we extended our research to screen the antitumor activity of two selected honey samples and eugenol (one of the phenolic constituents of honey) against murine Ehrlich ascites and solid carcinoma models. Honey containing higher phenolic content was found to significantly inhibit the growth of Ehrlich ascites carcinoma as compared to other samples. When honey containing higher phenolic content was given at 25% (volume/volume) intraperitoneally (i/p), the maximum tumor growth inhibition was found to be 39.98%. However, honey was found to be less potent in inhibiting the growth of Ehrlich solid carcinoma. On the other hand, eugenol at a dose of 100 mg/kg i/p was able to inhibit the growth of Ehrlich ascites by 28.88%. In case of solid carcinoma, eugenol (100 mg/kg; i/p) showed 24.35% tumor growth inhibition. This work will promote the development of honey and eugenol as promising candidates in cancer chemoprevention.